Cleanly housekeeping - Umberger, Grace E. (My University, 1905)
Introduction: By “Cleanly housekeeping” is meant, simply, first. The total removal of all dirt, dust and breeding places of bacteria and rendering it totally sanity in every respect, and, second-striving to keep the surroundings in such a condition. Besides the general poisonous effect of dirt and filth upon the body, it serves as food and protection for swarms of the tiny microscopic forms of life, and if care is not taken to keep the number of bacteria in check, they will soon rule the province and life cannot be sustained long. For the best growth of bacteria the following requisites are best: warmth, darkness, moisture, and filth. By guarding against these conditions, and, above all, avoiding dusty, dirty furniture and walls, they can be kept in check. First remove dirt and dust from rooms, then throw open windows and doors, and admit all the fresh air and sunshine that can be obtained as sunshine, in the proper amount is almost sure a preventative and means death to them.
Citation: Umberger, Grace E. Cleanly housekeeping. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Bacteria in the Kitchen; Bacteria on the Floors; Bacteria in Range Sink or Refrigerator; Theses; Manuscripts (documents)